(untitled) (National Administration Journal, 2019)
The study analyzes the requirements of companies regarding the training of professionals specialized in international management and identifies key aspects related to practical knowledge, technical training, skills and abilities. The methodology includes documentary reviews, interviews and a survey of the business sector via an online instrument. Therefore, the training of professionals in international business must be multidisciplinary and bilingual. Also, these need to develop their reasoning, leadership, communication, autonomy and innovation skills while taking advantage of disruptive technologies so that as graduates they may generate and implement knowledge.